y = -2x - 5
Step-by-step explanation:
We begin by finding the gradient of the line;
Δ y / Δ x
(1 – 3) / (-4 - -5)
-2 / 1
So the equation, to begin with, will be;
y = -2x + c
Let's find the value of C;
This is called the y intercept and is when x=0 at the intercept
(1,3) (0,c)
-2 = c – 3 / 0 – 1
-2 = c - 3 / -1
2 = c – 3
C = -3 – 2
C = -5
The final equation is;
y = -2x - 5
Learn More:
https://brainly.com/question/11505784
https://brainly.com/question/11267292
https://brainly.com/question/1372860
https://brainly.com/question/12582965
https://brainly.com/question/11661163
https://brainly.com/question/5368094
#LearnWithBrainly